2001
DOI: 10.1097/00001665-200105000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Resorbable Mesh in the Treatment of Orbital Floor Fractures

Abstract: A variety of materials have been used to reconstruct defects of the orbital floor. Autogenous materials such as bone and cartilage have the obvious drawback of the necessary donor site, whereas alloplastic implants carry the potential risk of infection, particularly when in communication with the maxillary sinus. Consequently, there has been interest in the use of resorbable alloplastic material that acts as a barrier until completely degraded. In this series, a total of 12 patients with orbital defects larger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 15 publications
2
55
1
2
Order By: Relevance
“…Polyglycolic acid is another resorbable alloplastic material, which has been evaluated in several clinical studies with different success rates. [15][16][17] Hollier et al 16 found some unsatisfactory results, including inflammatory reactions. However, McVicar, Hatton, and Brook 15 reported good results without any complications using polyglycolic acid membranes for orbital floor repair.…”
Section: Discussionmentioning
confidence: 99%
“…Polyglycolic acid is another resorbable alloplastic material, which has been evaluated in several clinical studies with different success rates. [15][16][17] Hollier et al 16 found some unsatisfactory results, including inflammatory reactions. However, McVicar, Hatton, and Brook 15 reported good results without any complications using polyglycolic acid membranes for orbital floor repair.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, the use of autogenic bone has been the gold standard in orbital wall reconstruction with cancellous bone, leading to a more complete repair than that achieved by cortical bone [9,10]. However, the harvesting of autogenous bone is associated with donor site morbidity, variable degree of resorption, and prolonged total operating time [11]. The use of synthetic materials instead of an allogenic material like lyophilized dura decreases the risk of biohazard infections [12].…”
Section: Introductionmentioning
confidence: 99%
“…Особенно чревато гнойными компликациями использование монолитных им-плантатов при наличии травматического соустья с верхнечелюстной пазухой [19].…”
Section: Discussionunclassified